How does the process of educational attainment differ between Africans and Coloureds in the Western Cape? - Hofmeyr, Clare (School of Economics, 2015)
More than a decade after the end of apartheid, inequality along racial lines is widely apparent. While the greatest disparity exists between Whites and non-Whites, inequality also persists among non-Whites. With reference to the youth of the Western Cape, Coloureds have higher per capita household income, more educated parents, superior schooling inputs and improved performance on achievement tests in comparison to Africans. The finding that Coloureds have only a slightly higher matriculation rate and a statistically equivalent enrolment rate leads one to ask whether the races face different influences on their process of educational attainment. Using individual and household data from the Cape Area Panel Study (CAPS), matriculation and enrolment (conditional on matriculation) are modeled for Africans and Coloureds separately.